(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to investigate family awareness of the concept of the child according to the variable of the number of children in the family. The researcher has developed a scale to assess this awareness. The researcher adopted the descriptive approach as a scientific methodology and relied on the integrative theory. After reviewing the relevant literature on children and families, a family awareness of the Child Concept Scale was developed, consisting of 37 items. The scale was first administered to a pilot sample to ensure the clarity of instructions. Subsequently, it was applied to a randomly selected sample of 300 children, and reliability was assessed using Cronbach alpha coefficient. The statistical analysis of the responses revealed that the level of family awareness among kindergarten children’s families was higher than the scale’s hypothetical mean, indicating a strong parental interest in understanding and addressing their children’s needs at this stage. Additionally, there was a statistically significant difference in family awareness based on the number of children within the household, suggesting that awareness levels vary according to family size.